(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
An earthquake with a magnitude of 5.6 occurred in Cianjur Regency. Not only having a physical impact, the earthquake that occurred in Cianjur also resulted in deep sorrow for the people of Cianjur. When conducting field surveys and observations, it was found that there was a crisis in Cianjur Regency. Responding to this, the PKM team at Putra Indonesia University and Jayabaya University carried out psychosocial support activities in four location areas consisting of Babakan Village, Sarongge Village, Kuta Village, and PasirChina Village. For psychosocial support to run well and smoothly, an appropriate communication strategy is needed. One of the communication strategies implemented by the PKM team with the survivors of the Cianjur disaster is empathetic communication. Empathic communication attitudes implemented include active listening, egalitarian, caring, eye contact, smiles, touches, and gentle words. The psychosocial support provided by the PKM team from Putra Indonesia University and Jayabaya University is hoped to be a means for residents and children to deal with stress and form resilience (ability to rise) which will become an asset when they face challenges in life in the future.